Knowledge Sharing, Human Capital, dan Kinerja UMKM: Studi Empiris pada UMKM di Kota Jayapura: (Knowledge Sharing, Human Capital, and MSME Performance:Empirical Study on MSMEs in Jayapura City) - Sylvia Christina Daat; Mariolin A. Sanggenafa (e-Journal Ekonomi Bisnis dan Akuntansi, 2022)
This study aims to obtain empirical evidence of the effect of knowledge sharing practices in MSMEs on improving MSME performance through the development of human capital as intellectual capital. This research is a quantitative research using primary data in the form of questionnaires distributed to SMEs in Jayapura. The research sample is 47 owners and management of SMEs in Jayapura. Research data processing using the SmartPLS statistical tool. The results of the study have not found empirical evidence of the positive influence of knowledge sharing activities on performance indirectly through human capital in MSMEs in Jayapura. However, the results of this study provide empirical evidence of the effect of knowledge sharing activities on increasing human capital. These findings indicate that intellectual capital spesifically human capital of MSMEs can be stregthened trough the practice of sharing knowledge.